Nonulosonic acids contribute to the pathogenicity of the oral bacterium Tannerella forsythia. Issue 2 (6th April 2019) - Bloch, Susanne; Tomek, Markus B.; Friedrich, Valentin; Messner, Paul; Schäffer, Christina
Abstract : Periodontitis is a polymicrobial, biofilm-caused, inflammatory disease affecting the tooth-supporting tissues. It is not only the leading cause of tooth loss worldwide, but can also impact systemic health. The development of effective treatment strategies is hampered by the complicated disease pathogenesis which is best described by a polymicrobial synergy and dysbiosis model. This model classifies the Gram-negative anaerobe Tannerella forsythia as a periodontal pathogen, making it a prime candidate for interference with the disease. Tannerella forsythia employs a protein O -glycosylation system that enables high-density display of nonulosonic acids via the bacterium's two-dimensional crystalline cell surface layer. Nonulosonic acids are sialic acid-like sugars which are well known for their pivotal biological roles. This review summarizes the current knowledge of T. forsythia' s unique cell envelope with a focus on composition, biosynthesis and functional implications of the cell surface O -glycan. We have obtained evidence that glycobiology affects the bacterium's immunogenicity and capability to establish itself in the polymicrobial oral biofilm. Analysis of the genomes of different T. forsythia isolates revealed that complex protein O -glycosylation involving nonulosonic acids is a hallmark of pathogenic T. forsythia strains and, thus, constitutes a valuable target for the design of novel anti-infective strategies to combat periodontitis.